Synthesis and Characterisation of Hierarchically Structured Titanium Silicalite‐1 Zeolites with Large Intracrystalline Macropores. Issue 63 (16th October 2019) - Weissenberger, Tobias; Leonhardt, Rainer; Zubiri, Benjamin Apeleo; Pitínová‐Štekrová, Martina; Sheppard, Thomas L.; Reiprich, Bastian; Bauer, Jürgen; Dotzel, Ralf; Kahnt, Maik; Schropp, Andreas; Schroer, Christian G.; Grunwaldt, Jan‐Dierk; et al.
Abstract: The successful synthesis of hierarchically structured titanium silicalite‐1 (TS‐1) with large intracrystalline macropores by steam‐assisted crystallisation of mesoporous silica particles is reported. The macropore topology was imaged in 3D by using electron tomography and synchrotron radiation‐based ptychographic X‐ray computed tomography, revealing interconnected macropores within the crystals accounting for about 30 % of the particle volume. The study of the macropore formation mechanism revealed that the mesoporous silica particles act as a sacrificial macropore template during the synthesis. Silicon‐to‐titanium ratio of the macroporous TS‐1 samples was successfully tuned from 100 to 44. The hierarchically structured TS‐1 exhibited high activity in the liquid phase epoxidation of 2‐octene with hydrogen peroxide. The hierarchically structured TS‐1 surpassed a conventional nano‐sized TS‐1 sample in terms of alkene conversion and showed comparable selectivity to the epoxide. The flexible synthesis route described here can be used to prepare hierarchical zeolites with improved mass transport properties for other selective oxidation reactions. Abstract : Inverse crystallisation : Hierarchical titanium silicalite‐1 zeolites with large intracrystalline macropores can be prepared by using mesoporous silica particles as sacrificial template. Interestingly, the zeolite growths in the interparticle voids around the steadily dissolving silica particles resulting in zeolite crystals, which represent the inverse of the initial packing of mesoporous particles.